DYNAMICS OF BODY COMPOSITION PARAMETERS IN WOMEN WITH METABOLIC SYNDROME IN THE POSTPARTUM PERIOD AFTER CAESAREAN SECTION UNDER THE INFLUENCE OF PHYSICAL THERAPY - Sheremeta, L. M.; Ostapiak, Z. M. (Rehabilitation and Recreation, 2023)
Purpose: to determine the effectiveness of restoring the health status of women with metabolic syndrome who underwent cesarean section, according to the dynamics of the parameters of the component composition of the body. Material. During the research, 44 women were examined at the end of the late postpartum period. The control group consisted of 17 women with normal body weight who gave birth vaginally. The comparison group consisted of 14 women with metabolic syndrome after caesarean section who recovered independently. The research group consisted of 13 women with metabolic syndrome after cesarean section, who for 3 months performed a physical therapy program (therapeutic exercises, functional training; pressotherapy; vacuum massage; nutritional recommendations). The anthropometric parameters (body mass index, the ratio of waist circumference to hip circumference) were studied, the content of fat, water, muscles, and visceral fat was determined by the bioimpedance method. Results. In women with metabolic syndrome and the consequences of caesarean section, a statistically significant deterioration of anthropometric parameters (increase in body mass index, ratio of waist circumference to hip circumference) and component body composition (decrease in muscle mass and water, increase in fat mass and visceral fat) relative to women with normal body weight who gave birth vaginally. The application of the physical therapy program led to the improvement of all components of the body according to all the studied parameters against the background of the tendency to improve anthropometric indicators. A low level of therapeutic/rehabilitation alliance resulted in unsatisfactory or non-compliance with the recommendations given by women in the comparison group, which was associated with a lack of improvement in their condition. In women with normal body weight, there were no changes in the studied indicators. Conclusions. Improvement of anthropometric indicators and body composition (percentage of muscle, water, subcutaneous and visceral fat) indicates sufficient effectiveness of physical therapy in correcting body weight in women with obesity in the postpartum period, although to achieve indicators of normal body weight and complete normalization indicators, the duration of restorative measures should be more than three months, and lifelong adherence to a balanced diet is required for all patients of this profile.